Outcomes and clinical predictors of improved survival in a patients undergoing pulmonary metastasectomy for sarcoma. Issue 1 (14th July 2015) - Dossett, Lesly A.; Toloza, Eric M.; Fontaine, Jacques; Robinson, Lary A.; Reed, Damon; Druta, Mihaela; Letson, Douglas G.; Zager, Jonathan S.; Gonzalez, Ricardo J.
<x xml:space="preserve">Abstract</x> Background Pulmonary metastasectomy (PM) for metastatic sarcoma can result in long‐term survival. The purpose of this study was to describe factors associated with survival in a series of patients undergoing PM for metastatic sarcoma. Methods We reviewed all patients undergoing PM for metastatic sarcoma over a 12‐year period (2000–2012). Multivariate analyses were used to identify factors associated with outcomes. Survival was calculated with Kaplan–Meier and Cox proportional hazard models. Results A total of 120 patients underwent PM with a median follow‐up was 48 months. Among 81 (85%) patients who presented with local disease, the median disease free interval (DFI) was 13 months and median overall survival (OS) was 48 months. Fourteen patients (15%) had synchronous metastasis with a median OS of 21 months. On multivariate analysis, synchronous metastasis (P = 0.005), older age (P = 0.02), and number of lung lesions (P = 0.003) were associated with poor survival. The median OS of patients with a DFI ≥12 versus <12 months following primary resection was 93 and 43 months (P = 0.004). Conclusion While patients with a DFI >12 months have the best OS following PM, patients with a DFI <12 months also have excellent outcomes as compared to systemic therapy and should be considered for PM. J. Surg. Oncol. 2015 111:103–106. © 2015 Wiley Periodicals, Inc.